2021
DOI: 10.17219/acem/135978
|View full text |Cite
|
Sign up to set email alerts
|

Role of resistin in cardiovascular diseases: Implications for prevention and treatment

Abstract: Cardiovascular diseases (CVDs) are associated with socioeconomic and, most importantly, with clinical problems. Accordingly, the identification of early and specific biomarkers indicating metabolic changes that underlie disease development and/or progression is important and may improve preventive and treatment strategies. A recently discovered protein -resistin (ADSF, FIZZ3) -whose expression is increased in carbohydrate metabolism and adipose tissue disorders, seems to be worth of interest in this context. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Several potential resistin receptors have been suggested but its specific one has not yet been identified and scarce information concerning the downstream signaling mechanisms of action is available (Badoer, 2021). Nevertheless, the hormone has been reported to be involved in a broad range of physiological and pathological conditions, both in rodents and in humans, acting centrally and peripherally (Aitken-Buck et al, 2020;Recinella et al, 2020;Deb et al, 2021;Rachwalik et al, 2021). In particular, resistin acting at the hypothalamic level influences energy homeostasis and modulates feeding, displaying anorexigenic effects in rodents (Brunetti et al, 2004;Tovar et al, 2005;Vázquez et al, 2008;Cifani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several potential resistin receptors have been suggested but its specific one has not yet been identified and scarce information concerning the downstream signaling mechanisms of action is available (Badoer, 2021). Nevertheless, the hormone has been reported to be involved in a broad range of physiological and pathological conditions, both in rodents and in humans, acting centrally and peripherally (Aitken-Buck et al, 2020;Recinella et al, 2020;Deb et al, 2021;Rachwalik et al, 2021). In particular, resistin acting at the hypothalamic level influences energy homeostasis and modulates feeding, displaying anorexigenic effects in rodents (Brunetti et al, 2004;Tovar et al, 2005;Vázquez et al, 2008;Cifani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In serum, it occurs as a dimeric protein composed of two 92-amino acid polypeptides linked by a disulfide bridge and its physiological concentration ranges from 7 to 22 ng/mL. In humans, monocytes are the main source, while in rodents, it is mostly produced by adipocytes [ 175 , 176 , 177 , 178 , 179 , 180 ]. It has been shown that in obese individuals, the resistin concentration is above the upper limit of reference values [ 181 ].…”
Section: Resistinmentioning
confidence: 99%
“…Resistin was discovered in 2001 by a group of researchers at the University of Pennsylvania. The name of this adipokine is derived from the phrase, "insulin resistance" [7]. It is produced by monocytes and macrophages as well as adipocytes, and its level rises with adipose tissue mass [8].…”
Section: Resistinmentioning
confidence: 99%
“…It was also proved that resistin is associated with recurrent cardiac events in patients' hospitalized for acute coronary syndrome (ACS) [11]. High resistin concentration in ACS was hypothesized to result from its release on atherosclerotic blood clot detachment [7], [12]. A heightened resistin level is predictive of not only coronary atherosclerosis but also recurrent stenosis after coronary stenting [13].…”
Section: Resistinmentioning
confidence: 99%